Strategies to improve tourism potentials in the east coast of jaffna peninsula - Kajentiny, K. (University of Jaffna, 2018)
This research tries to explore the possible strategies of improving the tourism based on the potentials of natural and environmental resources in the Eastern Coastal belt of Jaffna Peninisula which stretches from Point Pedro to Chundikulam. Though Jaffna Peninsula has many potentials for attracting tourism, the tourist arrival and income from the tourism sector remain insignificant due to marginal growth of the sector. People live in many parts of the Peninsula experience difficulties in finding economic opportunities. The regional development must be complemented by many development potentials and tourism is one of such potential which can trigger the development is tourism sector to address this issues of poverty. The spatial data on natural resources that are potentials for tourism in the coastal belt have been collected using high resolution satellite images using GIS techniques. All walk of the coastal areas were visited and observed to comprehend the potentialresources that could support the development of tourism. Data on infrastructures such as road networks from high resolution satellite images, hotels, and financial institutions from statistical handbook of Maruthankerny DS Office were collected. In addition, discussion with the stakeholders were used to collect about the potentials and strategies to improve the tourism sector. The resources and potentials suitable for tourism development were analyzed using SWOT analysis techniques. The coastal belt is having great natural potentials such as deep ocean edges, blue ocean fronts, golden beaches, sand dunes, natural vegetation and marshy lands, bird sanctuaries. The resources have strong attraction potentials but now they are idling and underutilized due to lack of planning initiatives. There are no adequate infrastructure facilities to support tourism sector and harness the potentials. The eastern coastal belt is poorly connected and creates the areas less accessible to the potentials sites. The eastern coastal belt does not have accommodation facilities, restaurant and financial institutions at appropriate locations to serve the visitors. There are no institutional mechanism and systems to guide the tourists and promote tourism. There is no policy related to tourism which will pave the way for promotion of tourism and economic development. A tourism master plan need to be developed to guide the relevant developments in the region. The plan shall have provisions to protect the natural resources and improve the environmental quality by implementing reforestation measures. Accommodation facilities at Kudathanai, Manalkadu, Ampan, Nargarkovil, Maruthankerny, Thalaiady, Vetilaikerny and Kaddaikadu will facilitate the tourists. The hotels with higher facilities can be accommodated in important places such as Maruthankerny and Iyakachchy and small hotels with less facilities can be established in other local places. There must be tourism informationCentre located in Iyakachchy and Point Pedro.
Keywords: Ecotourism; Tourism infrastructure; Natural resources; SWOT analysis